Mechanisms of exercise pressor reflex dysfunction in heart failure - Butenas, Alec Lloyd Edward (Kansas State University, 2023)
Heart failure patients with reduced ejection fraction (HF-rEF) have augmented sympathetic nervous system activity (SNA) at rest, and during exercise which is linked to decreased exercise tolerance and increased mortality. A reflex arising from within contracting skeletal muscles, termed the exercise pressor reflex, contributes importantly to that exaggerated SNA in HF-rEF. This reflex is activated when the sensory endings of thin fiber muscle afferents are stimulated by mechanical and/or metabolic signals associated with skeletal muscle contraction. Activation of this reflex in healthy subjects acts to increase and redistribute cardiac output and increase blood flow to the contracting skeletal muscles. Conversely, activation of this reflex in HF-rEF patients contributes to an exaggerated increase in SNA and augmented peripheral and coronary vasoconstriction and increases a heart failure patient’s risk of myocardial ischemia and fibrillation. Thus, in health the exercise pressor reflex functions to support the metabolic demands of exercise, whereas in HF-rEF the reflex becomes dysfunctional and impairs exercise tolerance. In this sequence of experiments presented in my dissertation, we used a rat model of myocardial infarction-induced HF-rEF (produced by coronary artery ligation). To isolate the exercise pressor reflex, we electrically stimulated the sciatic nerve to elicit hindlimb skeletal muscle contractions in decerebrated, unanesthetized rats. We also passively stretched the hindlimb skeletal muscle to isolate the activation of muscle afferents that are mechanically sensitive which allows us to study the mechanoreflex component of the exercise pressor reflex isolated from the metaboreflex component of the exercise pressor reflex. The contraction and stretch maneuvers produced an exaggerated increase in renal SNA (RSNA) and mean arterial pressure (MAP) in rats with HF-rEF compared to sham-operated control rats (SHAM rats). In the first study (chapter 2), we found that hindlimb arterial injection of a thromboxane A₂ receptor (TxA₂-R) antagonist reduced the RSNA and MAP response to muscle stretch in rats with HF-rEF, but not SHAM rats. In the second study (chapter 3), we found that hindlimb arterial injection of a TxA₂-R antagonist reduced the RSNA and MAP response to muscle contraction in rats with HF-rEF, but not SHAM rats. In the third study (chapter 4), we found that preventing translocation of protein kinase C subtype epsilon (PKC[subscript epsilon]), an important second messenger which is translocated to the cell membrane when G[subscript q] proteins, such as TxA₂-Rs, are activated, reduced the RSNA and MAP response to muscle contraction and muscle stretch in rats with HF-rEF, but not SHAM rats. In the final study, we found that hindlimb arterial injection of an acid-sensing ion channel subtype 1a (ASIC1a) antagonist reduced the RSNA and MAP response to muscle contraction and RSNA response to muscle stretch in rats with HF-rEF, but not SHAM rats. The culmination of these studies indicates that TxA₂-R and ASIC1a on the sensory endings of thin fiber muscle afferents as well as second messenger signaling involving PKC[subscript epsilon] within the sensory ending of these afferents, contributes importantly to evoking an exaggerated increase in SNA during exercise in HF-rEF consequent to mechanoreflex and exercise pressor reflex activation.
Keywords: Mechanoreflex; Metaboreflex; HF-rEF